The immune regulatory effects of tetrahedral framework nucleic acid on human T cells via the mitogen‐activated protein kinase pathway. (25th June 2021) - Liu, Xuyang; Yu, Zhiyuan; Wu, Ya; Shi, Sirong; Yao, Jie; Feng, Xiaorong; Wen, Dingke; Shi, Ziyan; Zhao, Zhengyang; Li, Yanjing; Zhou, Hongyu; You, Chao; et al.
Abstract: Objectives: Autoimmune diseases are a heterogeneous group of diseases which lose the immunological tolerance to self‐antigens. It is well recognized that irregularly provoked T cells participate in the pathological immune responses. As a novel nanomaterial with promising applications, tetrahedral framework nucleic acid (TFNA) nanostructure was found to have immune regulatory effects on T cells in this study. Materials and Methods: To verify the successful fabrication of TFNA, the morphology of TFNA was observed by atomic force microscopy (AFM) and dynamic light scattering. The regulatory effect of TFNA was evaluated by flow cytometry after cocultured with CD3+ T cells isolated from healthy donors. Moreover, the associated signaling pathways were investigated. Finally, we verified our results on the T cells from patients with neuromyelitis optica spectrum disorder (NMOSD), which is a typical autoimmune disease induced by T cells. Results: We revealed the alternative regulatory functions of TFNA in human primary T cells with steady status via the JNK signaling pathway. Moreover, by inhibiting both JNK and ERK phosphorylation, TFNA exhibited significant suppressive effects on IFNγ secretion from provoking T cells without affecting TNF secretion. Similar immune regulatory effects of TFNA were also observed in autoreactive T cells from patients with NMOSD. Conclusions: Overall, our results revealed a potential application of TFNA in regulating the adaptive immune system, as well as shed a light on the treatment of T cell–mediated autoimmune diseases. Abstract : Tetrahedral framework nucleic acid, as a novel nanomaterial, was used in human primary T cells for the first time. TFNA could regulate the immune response of T cells compared with immunosuppressors both in physiological and pathological circumstances via the MAPK signaling pathway. TFNA could regulate the immune response of T cells in peripheral blood of patients with NMOSD ex vivo.